Orbitally forced ice sheet fluctuations during the Marinoan Snowball Earth glaciation - Benn, Douglas; Le Hir, Guillaume; Bao, Huiming; Donnadieu, Yannick; Dumas, Christophe; Fleming, Edward J.; Hambrey, Michael J.; Mcmillan, Emily A.; Petronis, Michael S.; Ramstein, Gilles; Stevenson, Carl T. E.; Wynn, Peter M.; et al. (Nature Geoscience, 2015)
International audience